The oral cavity as a reservoir for resistance- and hypervirulence-associated genes of Klebsiella pneumoniae in hospitalized patients - Zenati, Karima; Braun, Sascha D.; Belhadi, Djellali; Moawad, Amira A.; Müller, Elke; Diezel, Celia; Brandt, Christian; Mostefaoui, Raouya; Monecke, Stefan; Zaidi, Fatma Zohra; Belmahdi, Mohamed; Touati, Abdelaziz; et al. (Frontiers in Microbiology, 2026)
IntroductionThis study investigated the epidemiology and distribution of carbapenem resistance and virulence genes in Klebsiella pneumoniae strains isolated from the oral cavity of hospitalized patients, highlighting their role as reservoirs in non-epidemic contexts.MethodsCarbapenem-resistant Klebsiella spp. were isolated from the oral cavity of 180 hospitalized patients in medical wards at two hospitals in Bejaia, Algeria. Screening for carbapenem resistance was performed on oral mucosa and saliva using Carba-MTL broth. Antibiotic susceptibility was assessed with the Vitek2 system and interpreted according to EUCAST guidelines. Whole genome sequencing (WGS) was carried out using Oxford Nanopore Technologies, with ABRicate used for resistance/virulence gene detection and Kleborate for hypervirulence assessment. Whole-genome sequences were further examined to identify single-nucleotide polymorphisms (SNPs) and to reconstruct a SNP-based phylogenetic tree in order to assess the genetic relatedness among the isolates.ResultsTwenty Klebsiella strains were identified as K. pneumoniae. Among these, 85% were carbapenem-resistant, carrying OXA-48 (80%) or NDM-5 (5%), and all harbored blaCTX-M-15. WGS of the 20 K. pneumoniae strains revealed a broad resistome, including β-lactamases (CTX-M-15, CMY-4, OXA-1, TEM-1), sulfonamide (sul1, sul2), aminoglycoside (aac(3)-IIa, aadA2, aph(3′)-VI, armA, strA, strB), trimethoprim (dfrA12, dfrA5, dfrA14), and tetracycline (tetA). Quinolone resistance was linked to QRDR mutations (gyrA S83I, parC S80I) and plasmid-mediated genes (qnrS1, qnrB10, qnrS10, aac(6′)-Ib-cr). Five distinct sequence types (STs) were identified, including high-risk clones ST13 and ST48. Virulence profiling revealed yersiniabactin (85%), frequently linked to ICEKp elements (ICEKp4, ICEKp10), and colibactin (40%) among OXA-48 isolates. Notably, a single K. pneumoniae isolate harboring NDM-5 (K21) carried both hypervirulence markers (ybt9/ICEKp3, iuc1, rmp1/kpvp-1) and carbapenem resistance, documenting, for the first time in Algeria, the convergence of these traits in oral isolates. ICEKp was identified as the key vehicle for dissemination of yersiniabactin and colibactin, and a novel association between ICEKp and kpvp-1 was observed. Capsular typing showed predominance of K57-O1/O2v2 among OXA-48 producers and K27/O4 among NDM-5 strains.ConclusionThis study provides the first evidence in Algeria of OXA-48- and NDM-5-producing K. pneumoniae in the oral cavity of hospitalized patients. The coexistence of carbapenem resistance and hypervirulence underscores the oral cavity as a critical reservoir, potentially fueling nosocomial infections and the dissemination of high-risk clones within hospitals and the wider community.